2023
DOI: 10.3126/rupantaran.v7i1.52208
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Mathematics Laboratory in School Level Education in Nepal

Abstract: The article explores the discourse of mathematics laboratories concerning classroom teaching. It focuses on the mathematics teachers' knowledge and awareness about the use of mathematics laboratories and their importance, especially in school-level education in Nepal. The study is descriptive in nature. It is chiefly based on the review of previous literature. This article presents a short glimpse into mathematics education, teaching mathematics, and an outline of mathematics laboratories precisely. It also di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…g] kfnL ;dfhdf ul0ft ;DaGwL w] /} :jb] zL1fg (Indigeous knowledge)5 o;n] ] ljBfyL{ x¿nfO{ JolQmut ¿kdf jf ;fyLx¿;F u ldn] / :yfgLo 1fg cWoog ug{ sIffsf] 7fdf 5nkmn ug{ tyf kl/of] hgf sfo{ sf] dfWodaf6 ;xh ?kdf ul0ft l;Sg d2t k' Ub5 (Panthi & Belbase, 2017) . Kunwar (2023) (Amit & Abu Qouder, 2015;Fouze & Amit, 2018). of] sIffsf] 7fdf ul0ft jf ;d' bfodf ul0ft x' g ;S5 eg] csf] { ;DalGwt :t/df of] ljlzi6 z} nLaf6 ul0ftnfO{ u0fgf ug] { , gfKg] , juL{ s/0f ug] { , qmda4 ug] { , cg' dfg nufpg] / df] 8] lnª ug] { sfo{ x¿ ug] { tl/sf xf] (Fouze & Amit, 2018).…”
Section: ;Lldt Ifdtfmentioning
confidence: 99%
“…g] kfnL ;dfhdf ul0ft ;DaGwL w] /} :jb] zL1fg (Indigeous knowledge)5 o;n] ] ljBfyL{ x¿nfO{ JolQmut ¿kdf jf ;fyLx¿;F u ldn] / :yfgLo 1fg cWoog ug{ sIffsf] 7fdf 5nkmn ug{ tyf kl/of] hgf sfo{ sf] dfWodaf6 ;xh ?kdf ul0ft l;Sg d2t k' Ub5 (Panthi & Belbase, 2017) . Kunwar (2023) (Amit & Abu Qouder, 2015;Fouze & Amit, 2018). of] sIffsf] 7fdf ul0ft jf ;d' bfodf ul0ft x' g ;S5 eg] csf] { ;DalGwt :t/df of] ljlzi6 z} nLaf6 ul0ftnfO{ u0fgf ug] { , gfKg] , juL{ s/0f ug] { , qmda4 ug] { , cg' dfg nufpg] / df] 8] lnª ug] { sfo{ x¿ ug] { tl/sf xf] (Fouze & Amit, 2018).…”
Section: ;Lldt Ifdtfmentioning
confidence: 99%
“…The curriculum and teaching methodology should be changed to make them applicable, concrete, and easy. Kunwar (2020) explored those occupations and education of parents played a remarkable role in learners' achievement in mathematics. This study also found that students obtaining marks were directly related to their parent's occupations.…”
Section: Review Of Literaturementioning
confidence: 99%
“…This study found a similar conclusion. Kunwar (2020) revealed that employment and education of guardians showed a significant role in learners' good performance in mathematics. This study found supportive results with the learning environment affecting the student's enrollment.…”
Section: Descriptive Analysis Of Difficulty Of Subject Mattersmentioning
confidence: 99%
“…Liking or disliking mathematics depends on the positive or negative perception of mathematics of learners. Further, Kunwar (2020) argued that achievement in mathematics was found according to their education, and occupation is directly linked to their children's performance in mathematics. The education and occupation of parents play a significant role in the achievement in mathematics of their children.…”
mentioning
confidence: 99%